Ocular Infection Preceding Major Epidural Abscess - Liam Dunbar; Ryan Johnstone (Case Reports in Orthopedics)
Staphylococcal bacteremia is an important clinical entity. A 74-year-old lady presented with an isolated staphylococcal ocular infection; this was treated with a short course of antibiotics, a prolonged course of steroids, and discharge from hospital with outpatient clinic followup. She represented three weeks later to the emergency department with back pain, raised inflammatory markers, and positive blood cultures. On magnetic resonance imaging (MRI), an extensive epidural collection was seen. This was surgically decompressed, and she was treated with appropriate intravenous antibiotics. Despite a complicated postoperative course, she made an excellent recovery. This case reviews the important clinical and radiological features of the presentation of a major epidural abscess and it also suggests a potentially unusual primary source. The clinician is reminded to always have a high index of suspicion regarding staphylococcal bacteremia and the potential for seeding to the epidural space.